Two Novel π-Conjugated Fluorophores for Dye-Doped LC On-Off Photoluminescence Switching - Diana, Rosita; Panunzi, Barbara; Caruso, Ugo (Letters in Organic Chemistry, 2020)
Among various classes of Photoluminescent (PL) compounds, soft-matter based materials in which chromophores are embedded in a Liquid-Crystal (LC) host polymer prove to be very attractive in the production of flexible panels and on-off temperature switches. Actually, the obtainment of low cost, easily synthesizable, and stable organic molecules soluble in the LC matrix is a challenge for both scholars and technologists. Here we describe the synthesis of two new emissive dyes based on a dicyanophenylenevinylene and on a bis-azobenzene core whose PL properties were investigated as neat solids, in solution, and in particular in a dye-doped LC nematic polymer often employed in PDLC applications. 1H NMR and 13C NMR spectroscopy allow the characterization of all compounds Their thermotropic liquid- crystalline (LC) properties were examined by differential scanning calorimetry and polarizing optical microscopy. Photoluminescence properties were characterized by fluorescence spectra.
Keywords: Photoluminescent compounds